E-Learning Acceptance in Business Administration Department State Polytechnic of Banjarmasin - Hikmayanti Huwaida; Rofi’i; Sri Imelda; Said Muhammad; Heppy Mutammimah (Jurnal Multidisiplin Madani, 2023)
E-learning is learning using Internet media. Acceptance of E-learning at the Business Administration Department, State Polytechnic of Banjarmasin, is measured by the Technology Acceptance Model method. This research is descriptive and verification research. The sample is 171 people. The data analysis technique uses the Structural Equation Model. The study results show that perceived ease of use does not affect behavioral intention to use technology but attitudes toward using technology. Perceived enjoyment influences attitude towards using technology. Behavioral intention to use technology affects actual technology use but does not affect satisfaction. Attitude towards using technology affects actual technology use. Actual technology use affects satisfaction. The variables with the greatest direct effect are perceived enjoyment on attitude towards using technology, perceived ease of use on behavioral intention to use technology, attitude towards using technology on actual technology use, and actual technology use on satisfaction. The variables with the greatest total effect are perceived enjoyment on attitude, perceived ease of use on behavioral intention to use technology, attitude on actual technology use, and perceived enjoyment on satisfaction